Comparative behavior studies of growing dairy and beef bulls from two different breeds - RIBIKAUSKAS, V.; KUČINSKIENĖ, J.; ARNEY, D.; RIBIKAUSKIENĖ, D. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study aimed at comparing the behaviour of growing bulls from two different breeds – Lithuanian black and white (dairy cattle breed, n=22) and Aubrac (beef cattle breed, n=17). The hypothesis tested in this study was that breed differences would result in differences in the behaviour of the bulls and that a clear understanding of such differences could lead to improved husbandry to meet their needs. Animals were raised in insulated barn in pens with deep litter, both breeds under similar conditions (animals were 11 to 14 month old, each group in separate 100 m2 pen). Aubrac bulls spent more time in standing, ruminating, drinking and aggressive behaviour and less time in eating than the Lithuanian black and white bulls. There were no significant differences in lying and moving behaviour. These differences possibly related to different breed of animals, and should inform decision making about the management of the two breeds studied.